2016
DOI: 10.17219/acem/62239
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of the Efficacy of a Training Walking Program in Patients Recovering from Abdominal Aortic Aneurysm Surgery

Abstract: bidity and the additional risk factors related to them contribute to a high risk of operative and postoperative complications. The main objective of the physiotherapy after abdominal surgery is to prevent and treat the postoperative complications and functional disorders resulting from the elective operation.All around the world, an increasing occurrence of abdominal aortic aneurysm has been observed, partly due to the prolongation of human life span and partly due to the development of diagnostic methods. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 20 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…musculoskeletal, cardiovascular, falls) Subacute, rehabilitation ward 22, Exercise program, 80.8 (4.6) 25, Usual care, 81.6 (6.5) Within 2 days of A, < 48 h before D DEMMI s , EMS r , TUG h , BI e Good Tibaek [ 27 ] 2013 Various diagnoses (e.g. falls, respiratory, medicine) Subacute, geriatric rehabilitation ward 29, Progressive resistance strength training, 80 (6.5) 27, Usual care, 79 (7.5) Within 3 days of A, D TUG h , 30s-chair stand test, 10MWT g , BI e , Modified FAC p Good Wnuk [ 18 ] 2016 Abdominal aortic aneurysm surgery Subacute, general and vascular surgery ward 1. 15, Backward walking training, 68 (3) 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…musculoskeletal, cardiovascular, falls) Subacute, rehabilitation ward 22, Exercise program, 80.8 (4.6) 25, Usual care, 81.6 (6.5) Within 2 days of A, < 48 h before D DEMMI s , EMS r , TUG h , BI e Good Tibaek [ 27 ] 2013 Various diagnoses (e.g. falls, respiratory, medicine) Subacute, geriatric rehabilitation ward 29, Progressive resistance strength training, 80 (6.5) 27, Usual care, 79 (7.5) Within 3 days of A, D TUG h , 30s-chair stand test, 10MWT g , BI e , Modified FAC p Good Wnuk [ 18 ] 2016 Abdominal aortic aneurysm surgery Subacute, general and vascular surgery ward 1. 15, Backward walking training, 68 (3) 2.…”
Section: Resultsmentioning
confidence: 99%
“…Load was increased by a 0.5 kg sandbag and by an elastic band with different resistance when the patient reported that the load was easy or moderate on the modified Borg Scale and could do more than 15 repetitions. 4 50 28 (15) 62.5 Wnuk [ 18 ] 2016 Physiotherapy program: consisted of education, active exercises of the upper and lower extremities and backward or forward walking on an interval training cycle. Yes, intensity of the interval training cycle was adjusted to individual patient abilities based on a stress test and a calculated training heart rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Finally, one study was performed in both the preoperative and postoperative periods (preoperative and postoperative study). 30 The clinical trial authors also published three other articles based on the same studies: two 25,26 from Myers et al 11 and one 27 from Barakat et al 28 Table 7 describes the studies and their characteristics, including the reasons for inclusion or exclusion. 39 ; # Text quoted from Kothmann et al 29 ; ** Text quoted from Tew et al 18 ; † † Text quoted from Myers et al 11 ; ‡ ‡ Text quoted from Barakat et al 28 .…”
Section: ⨁◯◯◯mentioning
confidence: 99%
“…A recent systematic review, concluding that the effect of physical activity interventions on physical performance in older patients during hospitalization was uncertain, included 15 trials. 8 The interventions used in those trials varied considerably and comprised (supervised) physical exercise program(s) with mobility, flexibility, strength, balance, walking and functional exercises, [9][10][11][12][13][14][15][16][17][18][19] proprioceptive neuromuscular facilitation, 20 electrical stimulation, 21 vibration training 22 and horse riding stimulation. 23 Four RCTs published afterwards [24][25][26][27] investigated one or more (supervised) physical exercise program(s) including mobility, flexibility, strength, balance, walking and functional exercises.…”
Section: Introductionmentioning
confidence: 99%